The last ten years of legal interpreting research (2008-2017). A review of research in the eld of legal interpreting - Monteoliva-Garcia, Eloisa (Language and Law / Linguagem e Direito, 2018)
Despite the controversial discussion around the definition and extent of the role of interpreters in legal settings (Hale, 2008), academics, practisearchers and increasingly interpreter users seem to agree on the crucial role of legal interpreting for both institutional and non-institutional users. When a linguistic barrier exists, interaction in prisons, courtrooms, asylum hearings, or between police officers and victims, suspects or witnesses, relies on interpreters and is modified by the very bilingual and multicultural nature of the interpreter-mediated encounter. Legal interpreting is dependent upon legislative, political and socioeconomic changes, such as the adoption of interpreting regulations or changes in migration policies; and researchers are making admirable efforts for the professionalization of legal interpreting. This review article describes the evolution of research on legal interpreting during the past ten years (2008-2017), and analyses the trends emerging and the focal points of research activity in the field. For the purposes of this review, publications on legal interpreting were compiled (including court, police, prison, asylum, immigration and military interpreting), and a database was created. Overall, 464 publications were collected and coded per setting and main theme, and reviewed for identification of salient themes and trends